Cloning and Characterization of Low-Molecular-Weight Glutenin Subunit Alleles from Chinese Wheat Landraces (Triticum aestivum L.). (10th April 2014) - Si, Hongqi; Zhao, Manli; Zhang, Xin; Yao, Guoliang; Sun, Genlou; Ma, Chuanxi
Abstract : Low-molecular-weight glutenin subunits (LMW-GS) are of great importance in processing quality and participate in the formation of polymers in wheat. In this study, eight new LMW-GS alleles were isolated from Chinese wheat landraces ( Triticum aestivum L.) and designated as Glu-A3-1a, Glu-A3-1b, Glu-B3-1a, Glu-B3-1b, Glu-B3-1c, Glu-D3-1a, Glu-D3-1b, and Glu-D3-1c, which were located at the Glu-A3, Glu-B3, and Glu-D3 loci, respectively. Based on the proteins encoded, the number of deduced amino acids of Glu-B3 alleles was approximately 50 more than those of Glu-A3 and Glu-D3 alleles. The first cysteine of Glu-A3 and Glu-D3 alleles was located at the N-terminal domain, while that of Glu-B3 alleles was found in the repetitive domain, which may lead to the different functioning in forming disulfide bonds. All the eight genes were LMW-m types and the new allele of Glu-B3-1a which had nine cysteine residues may be the desirable LMW-GS gene for improving bread-making quality.